Body site‐specific genetic effects influence naevus count distribution in women. (25th August 2019) - Visconti, Alessia; Ribero, Simone; Sanna, Marianna; Spector, Tim D.; Bataille, Veronique; Falchi, Mario
Abstract: Body site is highly relevant for melanoma: it affects prognosis and varies according to the patient's sex. The distribution of naevi, a major risk factor for melanoma, at different body sites also varies according to sex in childhood. Using naevus counts at different body sites in 492 unrelated adults from both sexes, we observed that women have an increased number of naevi on the lower limbs compared to men ( p = 8.5 × 10 −5 ), showing that a high naevus count on this site persists from childhood throughout life. Then, using data from 3, 232 twins, we observed, in women, the lowest naevus count heritability on the trunk (26%), and the highest on the lower limbs (69%). Finally, we showed that, in 2, 864 women, six genomic loci previously associated with both naevus count and melanoma risk ( IRF4, DOCK8, MTAP, 9q31.2, KITLG and PLA2G6 ) have an effect on naevus count that is body site‐specific, but whose effect sizes are predominantly stronger on the lower limbs. Sex‐specific genetic influence on naevus count at different sites may explain differences in site‐specific melanoma incidence as well as prognosis between sexes.